Front Cover: Nonprecious‐metal Fe/N/C Catalysts Prepared from π‐Expanded Fe Salen Precursors toward an Efficient Oxygen Reduction Reaction (ChemCatChem 4/2018). Issue 4 (21st February 2018) - Tanaka, Yuta; Onoda, Akira; Okuoka, Shin‐ichi; Kitano, Tomoyuki; Matsumoto, Koki; Sakata, Takao; Yasuda, Hidehiro; Hayashi, Takashi
Abstract : The Front Cover illustrates the preparation of the Fe/N/C catalysts by pyrolysis of π‐expanded Fe(Salen) precursors for the oxygen reduction reaction (ORR). In their Full Paper, Y. Tanaka et al. demonstrate that the ligand frameworks of the precursors significantly affect the content of pyridinic N and the structure of atomically‐dispersed Fe active sites in Fe/N/C catalysts. Atomically‐dispersed Fe active sites with a high content of pyridinic N promote the efficient four‐electron reduction of dioxygen.